Hollow MoS3 Nanospheres as Electrode Material for "Water‐in‐Salt" Li–Ion Batteries. Issue 8 (27th April 2020) - Quan, Ting; Xu, Yaolin; Tovar, Michael; Goubard‐Bretesché, Nicolas; Li, Zhaolong; Kochovski, Zdravko; Kirmse, Holm; Skrodczky, Kai; Mei, Shilin; Yu, Hongtao; Abou‐Ras, Daniel; Wagemaker, Marnix; et al.
Abstract: The use of "water‐in‐salt" electrolyte (WISE) (i. e., a highly concentrated aqueous solution) in rechargeable batteries has received increasing attention due to the significantly expanded electrochemical window compared to the limited voltage of conventional aqueous electrolytes. It enables the use of more positive/negative electrode material couples in aqueous batteries, resulting in an enhanced output voltage. However, one of the challenges is to identify promising anode materials for the "water‐in‐salt" Li‐ion batteries (WIS‐LIBs). Herein we for the first time demonstrate that MoS3, an amorphous chain‐like structured transitional metal trichalcogenide, is promising as anode in the WIS‐LIBs. In this work, hollow MoS3 nanospheres were synthesized via a scalable room‐temperature acid precipitation method. When applied in WIS‐LIBs, the prepared MoS3 achieved a high specific capacity of 127 mAh/g at the current density of 0.1 A/g and good stability over 1000 cycles. During operation, MoS3 underwent irreversible conversion to Li2 MoO4 (with H2 S and H2 evolution) during the initial Li ion uptake, and was then converted gradually to a more stable and reversible Li x MoO y (2≤ y ≤4)) phase along cycling. Amorphous Li‐deficient Li x ‐ m MoO y /MoO z was formed upon delithiation. Nevertheless, MoS3 outperformed MoO3 in WIS‐LIBs, which could be accredited to its initial one‐dimensional molecular structure and the amorphous nature of the delithiated product facilitating charge transport. These results demonstrated a novel routine for synthesizing metal sulfides with hollow structures using a template‐based method and push forward the development of metal sulfides for aqueous energy storage applications. Abstract : A WISE choice : Hollow MoS3 nanospheres are synthesized via a scalable template‐based method to be used as anode for Li‐ion batteries (LIBs) using "water‐in‐salt" electrolytes (WISE). High specific capacity and excellent stability are achieved in WIS‐LIBs and the working mechanism of MoS3 in aqueous LIBs is reviewed.